Understanding barriers and facilitators to cervical cancer prevention among young Korean Women: A focus group interview study - Hyun Jin Kim; Hyeon Ji Lee; Hye Young Shin; Hye-Sun Lee; Jae Kwan Jun; Kui Son Choi; Mina Suh (PLoS ONE, 2026)
Cervical cancer is a largely preventable and controllable disease. Social perceptions regarding sexual experiences and gynecological visits contribute to stigma, which serves as a major barrier to screening and human papillomavirus vaccination. This study explored how stigma is formed and reinforced within sociocultural norms and personal psychological barriers. Focus group interviews were conducted with 14 Korean women aged 20–29 years, divided into screeners and non-screener groups, on November 23, 2024. Based on the transcriptions, Thematic analysis was performed on the transcripts to organize codes into core themes,(in compliance with qualitative research reporting standards). A total of 28 codes were grouped into 10 sub-themes and classified by group. Among them, three sub-themes were common to both screeners and non-screeners, including negative perceptions of gynecological visits, stigma associated with sexually transmitted diseases, and barriers due to a lack of information. Among screeners, four sub-themes were identified: a desire for alternative notification methods for screening, psychological barriers to screening, a sense of burden from additional tests during visits, and reluctance to share screening experiences due to perceived prejudice from others. Among non-screeners, three sub-themes were identified: stigma toward patients with cervical cancer and lack of awareness of the sensitivity of cervical cancer. To promote cervical cancer preventive behaviors, stigma must be addressed as a social process rather than solely an individual issue. Practical solutions include creating a predictable screening environment (e.g., prior notification of procedures and additional tests with consent), improving patient-centered care, and enhancing notification methods. This study provides a foundation for developing stigma-related indicators and designing follow-up studies. (e.g., individual interviews/large-scale surveys).